PLANNING: A VERITABLE TOOL FOR CURBING WASTAGE IN SECONDARY EDUCATION IN NIGERIA (UNIZIK Journal of Educational Management and Policy, 2018)
This paper highlighted the place of planning as a veritable tool in curbing wastages in secondary education in Nigeria. Within the framework of efforts and strategies towards curbing wastages in Nigerian secondary schools, planning is increasingly accepted as an important tool. Despite the efforts of the government and school management to curb wastages in secondary schools in Nigeria, the trend seems to be increasing resulting in high rate of school dropouts, repetition rates and unemployment among others. This paper reviewed the concept and forms of wastages, causes of wastages and the place of planning in reducing wastages. It is believed that effective planning on the efficient use of educational resources will go a long way towards curbing the increasing wastage rate in secondary schools in Nigeria. The paper recommended among others that there should be a periodic assessment plan to determine the needs of secondary education with a view to eliminating wastages due to repetition and dropout.
Keywords: Planning; Wastages; Repetition